When Playing Is a Problem: An Atypical Case of Alien Hand Syndrome in a Professional Pianist - Alfaro, Arantxa; Bernabeu, Ángela; Badesa, Francisco J.; García, Nicolas; Fernández, Eduardo (Frontiers in Human Neuroscience, 2017)
Alien hand syndrome is a neurological illness characterises by limb movements which are carried out without being aware of it. Many patients describe these movements as aggressive and some perceive a strong feeling of estrangement and go so far as to deny ownership. The sense of body ownership is the perception that parts of one’s body pertain to oneself, despite it is moving or not and if movement is intentional or unintentional. These anomalous self-experiences may arise in patients with focal brain lesions and provide unique opportunities to disclose the neural components underlying self-body perception. The feeling of foreignness described in alien hand syndrome is often observed in post-central cortical lesions in the non-dominant hemisphere and is typical of the ‘posterior alien hand variant’. We used Diffusion-Tensor magnetic resonance imaging in an unusual case of posterior alien hand syndrome of the dominant hand in a professional pianist with corticobasal syndrome. The patient showed uncontrolled levitation with the right arm while playing the piano and perceived as if her hand had a “mind of its own” which prevented her from playing. MRI-scans show asymmetric brain atrophy, mainly involving left post-central regions and SPECT-Tc99m-ECD patterns of hypometabolism over the left parietal-occipital cortices. Diffusion-Tensor magnetic resonance imaging revealed extensive damage which comprised left fronto-temporal cortex and extends into the ipsilateral parietal cortex causing a disruption of corpus callosum projections from the rostrum to the splenium. Our case illustrates that posterior alien hand syndrome may occur in the dominant hemisphere due to widespread damage, which exceed parietal cortex. The parietal lobe has been recognized as a multimodal association region that gets input from several networks and organises motor output. We suggest that the disturbance to this pathway could result in disruption of motor output and associate an abnormal motor control and anomalous self-body perception.